2013
DOI: 10.5603/kp.2013.0124
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between clinical parameters of periodontal disease and mean platelet volume in patients with coronary artery disease: a pilot study

Abstract: Chronic periodontitis in patients with CAD results in an increased MPV that may suggest increased platelet activity. This observation could indicate a potential pathophysiological link between chronic periodontitis and an increased risk of acute coronary syndromes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 20 publications
1
9
1
Order By: Relevance
“…In adolescents with mild periodontitis, a slight increase in MPV levels has been found . Higher MPV levels were found in previously diagnosed CAD patients with periodontitis compared to the control group, and significant correlations between clinical periodontal parameters (PD and CAL) and MPV were shown . A positive correlation between increased MPV and decreased PD after periodontal treatment in patients with severe periodontitis has also been shown …”
mentioning
confidence: 72%
See 1 more Smart Citation
“…In adolescents with mild periodontitis, a slight increase in MPV levels has been found . Higher MPV levels were found in previously diagnosed CAD patients with periodontitis compared to the control group, and significant correlations between clinical periodontal parameters (PD and CAL) and MPV were shown . A positive correlation between increased MPV and decreased PD after periodontal treatment in patients with severe periodontitis has also been shown …”
mentioning
confidence: 72%
“…reported decreased MPV levels in severe periodontitis patients compared to the control group and showed that the MPV levels increased after periodontal therapy in this study group. Androsz‐Kowalska et al . reported that MPV was significantly higher in the patients with previously diagnosed CVD and coexisting chronic periodontitis than that in the control group, and correlations between clinical parameters of periodontal disease and MPV in patients with coronary artery disease were found.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous papers have documented prognostic value of mean platelet volume (MPV) in cardiovascular pathology [1][2][3][4][5][6][7], including published research on correlation between MPV and periodontal disease (PDe) in coronary patients [8]. A thorough search on correlation between MPV and exacerbated heart failure revealed only 2 publications in this area [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, young patients with at least one risk factor for CAD should be closely monitored, and the prognostic value of non-cardiac conditions and gene polymorphism of the early onset and exacerbation of CAD is currently an active area of research [20,21].…”
Section: Discussionmentioning
confidence: 99%